Just sustainabilities: The case of eco-estates in South Africa. Issue 2 (1st February 2022) - Mistry, Anjali; Spocter, Manfred
ABSTRACT: Globally, gated communities have been associated with negative social, economic and environmental impacts that are not conducive to sustainable urban development. Eco-estates have been touted as the answer to these sustainability issues and are viewed as the new "green" gated communities. Nature is a key aspect of eco-estates as it promotes a back-to-nature narrative to homebuyers and promotes sustainable living. This paper investigates eco-estates in South Africa with a view to establish whether they really contribute to just sustainabilities, that is a nuanced framing of sustainable developmvnent that involves a focus on social and economic equity. The study posits that while green initiatives within eco-estates may play a part in sustainable development, they fall short of advancing a just sustainability. The inherent exclusionary nature of eco-estates perpetuates inequality as the access to sustainable living in eco-estates is premised on whether one can afford to buy into these estates. Just sustainabilities in eco-estates cannot be met unless interventions to widen the access to nature and sustainable living are implemented. Until then, eco-estates will remain islands of exclusion of nature and "green" living.